"3DMeshTracings": A protocol for the digital recording of prehistoric art. Its application at Almendres cromlech (Évora, Portugal). (June 2019) - Cerrillo-Cuenca, Enrique; Bueno-Ramírez, Primitiva; de Balbín-Behrmann, Rodrigo
Abstract: The recording of megalithic art on menhirs in Western Iberia used to be performed through direct tracing. The use of photographic techniques represented an important advance in the interpretation of some of the most important prehistoric sites in this wide region, and also in the structuring of archaeological narratives. With the development of photogrammetry, the possibilities have improved considerably, enabling the recording of decorations not visible to the naked eye. In this paper, we present a new protocol to highlight the engravings on eroded surfaces, based on High Performance Computing and advanced algorithms for 3D mesh calculation. This tailored protocol has rendered expressive visual results that have succeeded in recording one of the most exceptional cromlechs in Western Europe: Almendres (Portugal). The results have proved the efficiency of the method and the need to revisit the classic megalithic sites. Highlights: A method for speeding up the recording of megalithic art in complex sites is presented. Unpublished motifs and stelae at one of the most relevant sites in prehistoric Portugal (Almendres) have been discovered. Several phases of decoration, suggesting a diachronic reworking of the pieces that compose the cromlech have been identified. The new discoveries allow connections to be traced between Iberia, Brittany and Southern France during Late Prehistory